Not Lost in Translation: Hebrew Wordplay in Greek - Backfish, Elizabeth (The Biblical archaeology review, 2021)
How does Moses make his coffee? Hebrews it. What kind of man was Boaz before he was married? Ruthless. Bible puns are like pineapple on pizza: Some people love them, and some people find them absolutely abhorrent.